Impact of coal consumption, ecological footprint on economic growth: new evidence from top seventeen coal countries - Adeneye, Yusuf Babatunde; Rasheed, Shahida (Frontiers in Energy Research, 2025)
IntroductionThis study explores the long-run relationship between coal consumption, ecological footprint, and economic growth in 17 coal-dependent countries from 1980 to 2022. This study further examines how ecological footprint and fossil fuel (Coal consumption) influence economic growth across different economic and ecological contexts.MethodsThe study employs Fully Modified Ordinary Least Squares (FMOLS) and Dynamic Ordinary Least Squares (DOLS) estimators to assess long-run relationships. Additionally, the Three-Stage Least Squares (3SLS) method is used to address potential endogeneity and investigate bidirectional and directional relationships among variables. The sample is further categorized into developed vs. developing countries and ecologically surplus vs. ecologically deficient countries to assess heterogeneity in the findings.ResultsEmpirical results reveal significant positive relationships between coal consumption, ecological footprint and economic growth in developing and ecologically deficient countries. However, this empirical finding is insignificant in developed and ecologically surplus countries. Additionally, the 3SLS results uncover a bidirectional negative relationship between coal consumption and economic growth, alongside strong directional positive relationships between coal consumption and ecological footprint, and between ecological footprint and economic growth, both significant at the 1% level. Moreover, the Environmental Kuznets Curve (EKC) hypothesis holds true for developed countries.DiscussionThe findings suggest a strong dependence on coal-driven growth in developing and ecologically deficient nations, highlighting sustainability concerns. Policymakers are urged to initiate a gradual shift from fossil fuels, particularly coal, to renewable energy sources. Recommendations include the promotion of public-private partnerships in energy innovation, the implementation of regulatory frameworks for fossil fuel consumption, and the provision of financial incentives for renewable energy adoption. These measures are essential for aligning economic growth with environmental sustainability across diverse economic and ecological landscapes.